Politics of poverty alleviation programs in Nigeria: challenges and prospects - Musa, Umar Farouk; Abdullah, Mohamad Ainuddin Iskandar Lee; Wahid, Ratnaria (2016)
Poverty is a social evil that affects the economic growth and development of different countries. This paper uses literature and power theory to examine the politics of poverty alleviation before, during and after the implementation of the structural adjustment program in the Federal Republic of Nigeria. Findings from the study reveals that over fifteen poverty alleviation programs were implemented like National Poverty Eradication Program but poverty remains at an alarming rate in the country. However, many reasons were attributed to the perpetual economic, social, psychological and political denial in the country.The high rate of absolute and relative poverty is as a result of political instability, inadequate policy continuity, especially during the military era. Similarly, corruption, mismanagement of resources allocated for these programs, the social evils in the aspects of violence, terrorism, insurgencies, communal and inter-religious conflicts crippled the poverty reduction strategies.Economically, other factors include a fall in the prices of petroleum products which is the country`s main sources of revenue, the budget deficits to finance the poverty reduction.Consequently, the inadequate harmonization and collaborations between the all tiers of governments, private sector, civil society organisations had again contributed to the failures of economic intervention measures.The paper recommended for, Agricultural policies and agribusiness initiatives, provision of social amenities, revival of War Against corruption, institutionalization of vocational education and training centers and entrepreneurship innovation to serve as a noble solution heartrending paucity diminution in Nigeria.